PENINGKATAN KREATIVITAS ANAK MELALUI MODEL SCAFFOLDING PADA PEMBELAJARAN DI SEKOLAH PENYELENGGARA PROGRAM LAYANAN PESERTA DIDIK CERDAS ISTIMEWA BAKAT ISTIMEWA - Erik Wahyu Zaenal Qori (Balai Diklat Keagamaan Bandung, 2023)
This study seeks to identify alternative learning models to increase children's creativity in CIBI student service program schools. The approach utilized is a combined research method consisting of a qualitative research pattern and an exploratory research design. The research procedure consisted of two phases; the first phase entailed analyzing problems and potentials in the world of education, particularly in the CIBI student service program in West Java; the second phase involved drafting a learning model in the scaffolding model. For the second stage, the results of scaffolding model formulation in the field were being piloted as a limited test related to creativity. Calculating t-test (0.025) for a two-tailed test on the student distribution (t) dk = 37 yielded ttab = -2,026, indicating that the use of scaffolding increased the frequency distribution of creativity among students with strong academic credentials. The calculation hit = -5.32 is in the Ho rejection area, and statistical analysis using the t-test indicates that the model is quite effective in increasing creativity in learning at CIBI student service programs. This indicates that the discovered model can positively influence the creative development of children.Keywords: Constructivism; Creativity Scaffolding Model; Educational Management